The Essence of Holism and its Applicability to the Marx's Theory - Gradinarov, Borislav (Research Papers, 2018)
Despite the numerous attempts to assess Karl Marx's economic ideas over the past 150 years, they still spark controversy over their methodological nature and impact on modern economic science. Based on an analysis of the methodological features of holism, reductionism, economic determinism etc., the text argues that it is most appropriate to designate Marx's economic theory as a particulistical (from lat. particula - part, element). This is a research approach that assumes that some elements of the public system have a lasting and sustainable priority, play a leading role over others.
Keywords: Holism; Particulism; Economic history; Economic theory; Methodology; Economic determinism